Current Status of Newborn Screening in Southeastern Europe - Koracin, Vanesa; Mlinaric, Matej; Baric, Ivo; Brincat, Ian; Djordjevic, Maja; Drole Torkar, Ana; Fumic, Ksenija; Kocova, Mirjana; Milenkovic, Tatjana; Moldovanu, Florentina; Mulliqi Kotori, Vjosa; Nanu, Michaela Iuliana; et al. (Frontiers in Pediatrics, 2021)
Significant part of Southeastern Europe (with a population of 76 million) has newborn screening (NBS) programs non-harmonised with developed European countries. Initial survey was conducted in 2013/2014 among 11 countries from the region to assess the main characteristics of their NBS programs and their future plans. At that time, none of the countries had an expanded NBS program, while phenylketonuria screening was not introduced in four and congenital hypothyroidism in three of 11 countries. We repeated the survey in 2020 inviting the same 11 countries, adding Cyprus, Greece, Hungary and Malta (due to their geographical position in the wider region). The aims were to assess the current state, to evaluate the change in the period, and to identify the main obstacles impacting the implementation of expanded NBS and/or reaching a wider population. Responses were collected from 12 countries (with a population of 68.5 million). The results of the survey showed that the regional situation regarding NBS only modestly improved in this period. All of the surveyed countries except Kosovo screened for at least congenital hypothyroidism, while phenylketonuria was not screened in four of 12 countries. Croatia and Slovenia implemented an expanded NBS program using tandem mass spectrometry from the time of last survey. In conclusion, the current status of NBS programs in southeastern Europe is very variable and is still underdeveloped (or even non-existent) in some of the countries. We suggest establishing an international task-force to assist with implementation and harmonisation of basic NBS services where needed.